The role of self-concept and expectations in academic achievement: A preliminary study - Pettersson, Lin Elinor; Muñoz-Luna, Rosa María (My University, 2015)
As early career students face new challenges at university, the relationship between L2 skills and academic success depends upon self-perception to a greater extent than previously assumed. Up to the moment, most levelling courses have focused on developing students’ skills in specific subjects in order to bridge the gap between the knowledge that the high school alumni have and university teachers expect them to possess. Yet, early academic failure remains elevated. For this reason, we have decided to focus our English Degree levelling course on academic strategies, expectations and procedures with the aim to disclose the role of students’ self-perception on L2 performance in an academic context. We have designed a two-staged method consisting of a survey and a standardized placement test to measure learners’ self-perception. The results of both stages are measured by following a mixed method procedure, combining quantitative and qualitative analyses. Results show that there is a close relationship between students’ self-concepts, academic expectations, and final outcomes. When the learning of new contents occurs by means of a foreign language, the implications of learners’ confidence and their academic awareness are even clearer. Therefore, we conclude that learners’ self-concepts, and awareness of their academic expectations should play a key role in initial undergraduate training.
Keywords: Enseñanza superior; Self-concept; Expectations; L2 performance; Levelling course; Higher education; Learning experience